Association between vascular FDG uptake during follow-up and the development of thoracic aortic aneurysms in giant cell arteritis - Blockmans, Daniel; Moreel, Lien; Betrains, Albrecht; Vanderschueren, Steven; Coudyzer, Walter; Boeckxstaens, Lennert; Van Laere, Koen (Frontiers in Medicine, 2024)
Background: A positive PET scan at diagnosis was associated with a greater yearly increase in ascending and descending aortic diameter and thoracic aortic volume in patients with giant cell arteritis (GCA). Radiologic and histopathologic vascular abnormalities persist in a subset of treated patients despite clinical remission. The aim of this study was to evaluate the association between vascular FDG uptake during follow-up and the development of thoracic aortic aneurysms. Methods: We recently performed a prospective cohort study of 106 GCA patients, who underwent FDG PET and CT imaging at diagnosis and CT imaging yearly for a maximum of 10 years. In this post-hoc analysis, GCA patients who also have had FDG PET imaging during follow-up were included. PET scans were visually scored (0-3) at 7 vascular areas. PET scans were considered positive in case of FDG uptake ≥ grade 2 in any large vessel. Results: Eighty-eight repeat PET scans were performed in 52 out of 106 GCA patients, who were included in the original prospective cohort. Fifty-five (63%) PET scans were done at the time of a relapse and 33 (38%) were done while in remission. Nine out of ten patients with an incident thoracic aortic aneurysm had both a positive PET scan at diagnosis and during follow-up.In addition to the intensity and extent of the initial vascular inflammation, ongoing aortic inflammation may contribute to the development of thoracic aortic aneurysms in GCA. However, this hypothesis should be confirmed in prospective trials with repeat PET scans at predefined time points.